2009
DOI: 10.1016/j.jvs.2008.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Open abdomen treatment following endovascular repair of ruptured abdominal aortic aneurysms

Abstract: The use of standardized novel techniques and a treatment protocol and algorithm for OAT after eEVAR for RAAA were feasible and safe. It decreased the workload of the medical and nursing staff, enhanced patient comfort because the need for dressing changes was minimized, and likely contributed to lower overall mortality in RAAA patients. Delayed direct fascial closure was possible in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 39 publications
(40 reference statements)
1
66
1
9
Order By: Relevance
“…Del total de casos, entre un 10 y un 20% son cuadros graves y de estos un 30% muere en el transcurso de la primera semana de evolución, por distintas complicaciones y falla multiorgánica 38,69,[80][81][82][83][84][85][86][87][88][89] . Los factores de riesgo de mortalidad son la infección de la necrosis pancreática (NPI), la coexistencia de HIA y el SCA.…”
Section: B) Pancreatitis Aguda Grave (Pag)/necrosis Pancreática Infecunclassified
See 1 more Smart Citation
“…Del total de casos, entre un 10 y un 20% son cuadros graves y de estos un 30% muere en el transcurso de la primera semana de evolución, por distintas complicaciones y falla multiorgánica 38,69,[80][81][82][83][84][85][86][87][88][89] . Los factores de riesgo de mortalidad son la infección de la necrosis pancreática (NPI), la coexistencia de HIA y el SCA.…”
Section: B) Pancreatitis Aguda Grave (Pag)/necrosis Pancreática Infecunclassified
“…c) Isquemia mesentérica aguda Entre las catástrofes quirúrgicas abdominales, la isquemia mesentérica aguda grave tiene una de las tasas más altas de morbimortalidad 75,87 . Los retrasos en el diagnóstico aumentan el ya grave compromiso fisiológico asociado con la patología primaria.…”
Section: De Tal Manera El Compartimento Inframesocolónico Queda Aislunclassified
“…It has a particularly relevant role following open repair for a ruptured aneurysm. Recording an intra-operative abdominal pressure of 12mmHg or above is described as an indication for this (Mayer et al, 2009). Here, it has been shown that in cases of ruptured AAA there is a 30% reduction in mortality associated with ACS using this technique (Mayer et al, 2009).…”
Section: Managementmentioning
confidence: 99%
“…The use of a simple sterile plastic drape or bag allows for direct visualisation of the bowel and other intra-abdominal contents and is a convenient manner of observing for impending bowel ischaemia in a patient where this is a significant concern. A Bogota bag serves the same purpose, however it also has extra reserve capacity in that it allows for further intra-abdominal swelling to take place without impacting on venous return to the heart and general visceral perfusion (Mayer et al, 2009). In cases where a simple plastic bag or drape or the Bogota bag has been employed these temporary closure devices can be changed to a VAC closure device or a zip device at a later stage.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation